2004
DOI: 10.1242/dev.01143
|View full text |Cite
|
Sign up to set email alerts
|

Cell-autonomous roles of theecdysonelessgene inDrosophiladevelopment and oogenesis

Abstract: Steroid signaling underlies developmental processes in animals. Mutations that impair steroidogenesis in the fruit fly Drosophila melanogasterprovide tools to dissect steroid hormone action genetically. The widely used temperature-sensitive mutation ecdysoneless1(ecd1) disrupts production of the steroid hormone ecdysone, and causes developmental and reproductive defects. These defects cannot be satisfactorily interpreted without analysis of the ecdgene. Here, we show that ecd encodes an as yet functionally und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
87
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 91 publications
(93 citation statements)
references
References 51 publications
5
87
0
1
Order By: Relevance
“…This may be a consequence of the lack of data from genome-wide analyses for the ring gland, coupled to the fact that the characterization of differential patterns of gene expression in the ring gland has been impaired by the small size of this organ (Niwa et al, 2004). Most of the genes that were shown to be expressed in the ring gland are related to the ecdysone biosynthetic pathway (Freeman et al, 1999;Gaziova et al, 2004;Gilbert, 2004;Neubueser et al, 2005;Warren et al, 2001;Yoshiyama et al, 2006), and were not identified in our analysis. Because in transgenesis the pattern of BhC4-1-lacZ expression driven by the 67 bp (2253/2187) fragment is distinct from the expression pattern of the genes that participate in ecdysone biosynthesis, it is possible that our study has revealed a hitherto uncharacterized set of genes which are coexpressed in the ring gland of late embryos.…”
Section: The Bioinformatics Analysis Identified Conserved Cis-regulatmentioning
confidence: 85%
See 1 more Smart Citation
“…This may be a consequence of the lack of data from genome-wide analyses for the ring gland, coupled to the fact that the characterization of differential patterns of gene expression in the ring gland has been impaired by the small size of this organ (Niwa et al, 2004). Most of the genes that were shown to be expressed in the ring gland are related to the ecdysone biosynthetic pathway (Freeman et al, 1999;Gaziova et al, 2004;Gilbert, 2004;Neubueser et al, 2005;Warren et al, 2001;Yoshiyama et al, 2006), and were not identified in our analysis. Because in transgenesis the pattern of BhC4-1-lacZ expression driven by the 67 bp (2253/2187) fragment is distinct from the expression pattern of the genes that participate in ecdysone biosynthesis, it is possible that our study has revealed a hitherto uncharacterized set of genes which are coexpressed in the ring gland of late embryos.…”
Section: The Bioinformatics Analysis Identified Conserved Cis-regulatmentioning
confidence: 85%
“…The molting defective (mld) (Neubueser et al, 2005) and without children (woc) (Warren et al, 2001) genes encode putative transcription factors that are expressed in the ring gland and several other tissues throughout development, for which the target genes have not been identified. The Drosophila genes, such as dare (Freeman et al, 1999), disembodied (dib), shadow (sad) (Gilbert, 2004), ecdysoneless (ecd1) (Gaziova et al, 2004), and neverland (nvd) (Yoshiyama et al, 2006), are all involved in ecdysteroids biosynthesis and are expressed both in the larval ring gland and in adult ovaries, which is the adult source of ecdysteroids. To our knowledge, the BhC4-1 67 bp ring gland enhancer is the only enhancer so far identified, which is able to drive developmentally regulated gene expression solely in the ring gland.…”
Section: The Bhc4-1 Promoter Region Contains Both a Ring Gland And A mentioning
confidence: 99%
“…2G). ecdysoneless (ecd 1 , Gaziova et al, 2004) females showed a similar eggshell phenotype when shifted to the restrictive temperature for 24 hr (Fig. 2H), indicating this phenotype is associated with reduced ecdysone signaling in the egg chamber.…”
Section: Slbo26gal4 Uas-ecrmentioning
confidence: 86%
“…At stage 8, ecdysone controls a check-point regulating egg chamber maturation. Complex interactions among genes required for ecdysteroid biosynthesis and isoforms of Br-C, Eip75B, and EcR mediate a physiological feedback to a direct a choice to develop or degenerate by apoptosis (Buszczak et al, 1999;Gaziova et al, 2004;Bownes, 2005, 2006;.…”
Section: Introductionmentioning
confidence: 99%
“…In other insects, the sex-specific killing action by Wolbachia occurs during embryogenesis (Dyer& Jaenike, 2004;Fialho & Stevens, 2000;Jiggins et al, 2001;Zeh et al, 2005). Embryogenesis takes place in a steroid hormone-enriched environment where steroid hormones act for the coordination of morphogenetic movements (De Loof, 2006;Kozlova & Thummel, 2003;Gaziova et al, 2004). Thus, if male-killing Wolbachia interacts with the host hormonal pathway involving ecdysteroids, this could interfere with the processes required for a normal development of males.…”
Section: Wolbachia and The Feminization Of The Arthropod Hostmentioning
confidence: 99%